Study Music for "Xian Qi Ni De Gai Tou Lai" in Uygur at Xin Jiang Province, the People's Republic of China - Ye, Zhu; Meeson, Pranote (Asia Pacific Journal of Religions and Cultures, 2024)
The objectives of the study are: 1) To study music for “xian qi ni de gai tou lai” in uygur at xin jiang province, the people’s republic of China 2) To create a guide book music for “xian qi ni de gai tou lai” in uygur at xin jiang province, the people’s republic of China. This research was conducted qualitatively, Collect data by interview three experts. Teacher interviews and review of the literature allowed for the development of a guide book, and the validity of the material was determined by experts (IOC), which can guide students to better mastery of learning Xinjiang Uyghur music and style genres. Results: The relationship between dance and music is very close, and the two complement and promote each other. The mutual combination of music and dance can make the art of music and dance richer, as well as better meet people's multifaceted aesthetic needs. Both music and dance have a certain rhythm, and in the process of artistic performance, both need to express certain emotions and themes, so it is said that music and dance are common, and only when the two achieve a perfect combination can they bring people visual and aural enjoyment and promote spiritual and cultural development. At the end of the teaching experiment, students of Zaozhuang Economic School made great progress in learning the Xinjiang Uyghur music and dance course "xian qi ni de gai tou lai".